PENGEMBANGAN MEDIA PEMBELAJARAN MONOKEBU UNTUK MENINGKATKAN LITERASI BUDAYA SISWA KELAS IV SEKOLAH DASAR - Zita Andini Sabillah; Ira Restu Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The limited understanding of Indonesian culture among elementary students reflects low cultural literacy, posing a challenge in learning environments that lack interactive media. This study aimed to evaluate the effectiveness of Monokebu, a board game-based learning medium, in enhancing the cultural literacy of fourth-grade students. The research used a Research and Development (R&D) approach with the ADDIE model, consisting of five phases. Monokebu was designed as an educational game adapted from the Monopoly concept, incorporating local cultural content from Indonesia. Validation results indicated high feasibility, with expert ratings of 92% (content), 98% (language), and 96% (media). A trial conducted at SDN Kampung Melayu 01 Pagi showed a significant improvement in students' understanding of cultural diversity. These findings confirm that Monokebu is an effective instructional tool for supporting IPAS learning objectives and highlight the importance of game-based media innovation as a more contextual, engaging, and interactive approach to cultural education in primary schools.